The Impact of Human Capital on Economic Growth: Evidence from Tunisia Using Star and Stecm Models - Mgadmi, Nidhal; Rachdi, Houssem (The Economics and Finance Letters, 2014)
Human capital is one of the most important drivers for economic growth. This paper aims to outline theoretical and empirical frameworks for thinking about the role of human capital in a model of endogenous growth. Only a small set of recent papers investigated the relationship between different educational levels and economic growth in one country. This first study conducted in Tunisia contributes to the existing literature by using Smooth Transition Autoregressive models (ESTAR, LSTAR) referring to non-linear least squares (NOLS) procedure to underline this non-linear relationship. The advantage of our modeling strategy is that the relationship between human capital and growth is nonlinear. The principal empirical finding conducted in Tunisia over the period 1974-2012 is that human capital exerts a significant influence on economic growth.